2017
DOI: 10.7554/elife.24081
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of the thin and thick filaments to length-dependent activation in heart muscle

Abstract: The Frank-Starling relation is a fundamental auto-regulatory property of the heart that ensures the volume of blood ejected in each heartbeat is matched to the extent of venous filling. At the cellular level, heart muscle cells generate higher force when stretched, but despite intense efforts the underlying molecular mechanism remains unknown. We applied a fluorescence-based method, which reports structural changes separately in the thick and thin filaments of rat cardiac muscle, to elucidate that mechanism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 67 publications
6
67
3
Order By: Relevance
“…thick filament regulation mechanisms) from the thin filament-based regulation mechanisms. This speculation is consistent with the recent study by Zhang et al (2017) which shows distinctive effects of SL on thin and thick filaments [27]. Specifically, they found that the SL-induced structural changes in Tn are distinct from those caused by Ca 2+ activation or strongly bound cross-bridges, and SL-induced structural changes in myosin is responsible for the increased maximal force.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…thick filament regulation mechanisms) from the thin filament-based regulation mechanisms. This speculation is consistent with the recent study by Zhang et al (2017) which shows distinctive effects of SL on thin and thick filaments [27]. Specifically, they found that the SL-induced structural changes in Tn are distinct from those caused by Ca 2+ activation or strongly bound cross-bridges, and SL-induced structural changes in myosin is responsible for the increased maximal force.…”
Section: Discussionsupporting
confidence: 92%
“…However, the underlying mechanism of LDA is still unknown. Different characteristics of the myofilaments contribute to LDA, such as the inter-filament lattice spacing [2426], the distinctive structural changes in thick and thin filaments [27, 28], the orientation and number of cross-bridges [2931], titin-based passive tension [3237], and the increase in positive feedback on myocardial contractile regulation [3840]. Our previous studies have shown that Ca 2+ -induced opening of the N-domain of cTnC [40], and Ca 2+ -induced movement of C-terminus of cTnI [41] are both SL- and cross-bridge-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no change in the Ca 2+ cooperativity, Hill coef icient, the length induced shift to lower [Ca 2+ ] activation is simply the result of raising the effective Ca 2+ af inity of either the cTn-C or the MgADP-phosphomyosin [5,6,8,9]. A recent study by Zhang, et al [14], with structural sensitive probes indicates that it is changes in the myosin head region, myosin light chain 2 (MLC2), that are responsible for the stretch induced ampli ication of maximal tension. Thus it is not the thin ilament cTn-C Ca 2+ af inity but the increase in MgADP-phosphomyosin af inity for Ca 2+ that is key to length induced activation.…”
Section: The Limits To Effectors In Fslhmentioning
confidence: 97%
“…The length-dependent activation (LDA) of myocardial contractility plays an important role in the adaptation of ventricular systolic pressure to the changes in end-diastolic ventricular volume. LDA constitutes the Frank-Starling Mechanism (FSM) and in normal myocardium is regulated by numerous well-tuned mechanisms, including myofilamental Ca 2+ sensitivity (Dobesh et al, 2002), coordinated actomyosin interaction (Farman et al, 2011;Milani-Nejad et al, 2015;Zhang et al, 2017), giant protein titin (Cazorla et al, 2001;Fukuda and Granzier, 2004;Li et al, 2019), and the phosphorylation of myosin binding protein C and regulatory protein troponin (Korte et al, 2012;Wijnker et al, 2014;Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%